Rationalising fertiliser subsidy in India: Key issues and policy options - Ashok Gulati; Pritha Banerjee (Indian Council for Research on International Economic Relations (ICRIER), 2015)
Given the importance of agriculture in any sizable country to feed its people, most countries have subsidised agriculture in the past, be they developed countries like the United States of America or countries in the European Union or Japan and Korea, or now emerging economies like China and India. The type of support, of course, varies widely across countries. The Government of India (GoI) has supported agriculture through budgetary provisions as well as through revenues foregone and a sizeable portion of budgetary support goes towards fertiliser subsidy. Fertiliser subsidy in India has succeeded in achieving its objective of increasing fertiliser consumption in agriculture and hence, raising food production, but it has also led to some problems because some fertiliser products have been priced very low. There are three key issues with regard to fertiliser subsidy in India: (1) rising amounts of fertiliser subsidy in the budget and how far they are financially sustainable; (2) extremely low prices of urea leading to imbalanced use of N, P and K, as also misuse of urea (like diversion to neighbouring countries and its use for non-agricultural purposes); and (3) lack of investment flows to the sector at home, leading to rising imports in the wake of uncertainty on fertiliser subsidy policy issues and delayed payments to industry. [...]
Keywords: I38; Q15; Q18; 330; Fertiliser; Subsidy; Agriculture; India; Cash Transfer